HUBUNGAN KOMPETENSI PEDAGOGIK DENGAN MOTIVASI DAN HASIL BELAJAR SISWA SMA NEGERI DI WATAMPONE - Nurwaida Faal Santri (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This study aimed at examining (1) significant correlation of pedagogy competence of Biology teacher toward student’s learning result both directly and indirectly through student’ learning motivation. (2) significant correlation between pedagogy competence of Biology teachers and students’ learning motivation; (3) significant correlation between pedagogy competence of Biology teachers and student’s learning result. This study is an ex-post facto. The population of the study were the entire students at SMAN in watampone of academic year 2013/2014. The samples were taken by employing random class technique with as many as 496 students. Data were collected through questionnaire and documentation. Data were analyzed using reggressin test and path analysis. The results of the study were (1) pedagogy competence gave influence directly to learning result with coefficient path (p) by 16.5%; whereas,it gave influence indirectly to learning motivation by 42.6% (2) there was correlation (p < 0.05) between pedagogy competence and students’ learning result on biology subject at SMAN in Watampone with coefficient (r) by 64.3%; (3) there was correlation (p < 0.05) between pedagogy competence and students’ learning motivation at SMAN in watampone with coefficient correlation (r) 64.1%;